2018
DOI: 10.21037/qims.2018.02.01
|View full text |Cite
|
Sign up to set email alerts
|

3D bone texture analysis as a potential predictor of radiation-induced insufficiency fractures

Abstract: Background: The aim of our work is to assess the potential role of texture analysis (TA), applied to computed tomography (CT) simulation scans, in relation to the development of insufficiency fractures (IFs) in patients undergoing radiation therapy (RT) for pelvic malignancies. Methods:We analyzed patients undergoing pelvic RT from Jan-2010 to Dec-2016, 31 of whom had developed IFs of the pelvis. We analyzed CT simulation scans using LifeX Software © , and in particular we selected three regions of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Recently, some researchers have been studying the application of computed tomography in measuring bone strength and predicting fracture [22], [23], [24]. These studies have shown that in addition to measuring BMD for detecting osteoporosis, QCT has the unique ability to provide information on anatomical morphology and get many quantitative parameters about bone health with a single scan, without causing pain due to movement especially in the elderly and those with fractures (such as identifying the details of vertebral fractures [25]).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have been studying the application of computed tomography in measuring bone strength and predicting fracture [22], [23], [24]. These studies have shown that in addition to measuring BMD for detecting osteoporosis, QCT has the unique ability to provide information on anatomical morphology and get many quantitative parameters about bone health with a single scan, without causing pain due to movement especially in the elderly and those with fractures (such as identifying the details of vertebral fractures [25]).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis can use multiple mathematical models that are aimed to provide quantitative parameters within a selected image, which are called texture features. TA is performed employing a computer quantification of both the gray-level intensity and position of the pixels, and its use is being investigated in several fields [ 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. More recently, a different approach to TA was developed, taking into consideration the variations in TA parameters at different acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…TA is performed by means of a computer quantification of both gray-level intensity, position of pixels, and its use is being investigated in several fields (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%